2019
DOI: 10.1590/1678-4162-10205
|View full text |Cite
|
Sign up to set email alerts
|

Beef cattle performance on signal grass pastures deferred and fertilized with nitrogen

Abstract: The effect of four nitrogen levels (0, 40, 80 and 120kg N ha-1), applied before deferment on the beef cattle production and structural variables on Urochloa decumbens (signal grass) were assessed from January to October 2012 and from January to September 2013. A randomized block design with three replicates was adopted, in an arrangement of repeated measures in time (grazing period). An interaction effect between nitrogen level and grazing period was observed on extended-plant height and herbage mass. As the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Associated with inadequate management, climatic seasonality is one of the factors that affect support capacity, resulting in production seasonality and negatively affecting animal weight gain by reducing forage yield and quality (AMORIM et al, 2019;SOUZA SOBRINHO et al, 2011). The improved pasture allows mitigating the effects of forage production seasonality, especially through the consortium with forage legumes (PEREIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Associated with inadequate management, climatic seasonality is one of the factors that affect support capacity, resulting in production seasonality and negatively affecting animal weight gain by reducing forage yield and quality (AMORIM et al, 2019;SOUZA SOBRINHO et al, 2011). The improved pasture allows mitigating the effects of forage production seasonality, especially through the consortium with forage legumes (PEREIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fertilization before pasture deferment can improve the forage mass and its chemical composition. In a study of deferred signal grass [5], the authors observed an increase in forage mass and an improvement in structural characteristics as the nitrogen dose increased, while increases in mass and allowance forage were identified [6]. However, nitrogen fertilization considerably increases the costs of production, as the synthesis of fertilizers requires sources of fossil fuel, and most nitrogen inputs are currently imported [7].…”
Section: Introductionmentioning
confidence: 99%